Creep Resistance of Polyethylene-based Nanocomposites - Alghamdi, A. S. (Engineering, Technology & Applied Science Research, 2019)
The purpose of this work is to investigate the effects of carbon black (CB), carbon nanotubes (CNTs) and nanoclay sheets addition on the creep behavior of polyethylene-based nanocomposites synthesized with an in-house processing method. A blend of 75 wt.% UHMWPE and 25 wt.% HDPE, abbreviated to U75H25, was used as the hybrid PE matrix to accommodate the nanofillers. A 0.5 wt.% of CB, CNTs or nanosheets clay was embedded separately into the blend matrix in order to improve the creep resistance. The scanning electron microscope (SEM) and transmission electron microscope showed that the nanofillers were homogeneously dispersed in the U75H25. The addition of just 0.5 wt.% nanoclay resulted in a significant increase in the creep resistance of the polyethylene blend. Conversely, the addition of CB or CNTs caused a reduction in the creep resistance. The embedding of CNTs into the matrix resulted in creep behavior almost close to the creep behavior of pure UHMWPE. The Burger’s model was employed to understand the effect of the nanoparticle addition on the creep mechanism.